Implications of the Drama of Jesus' Passion Story in the Gospel of John for the Ethics of the Political Elite in the Public Sphere - Mathias Jebaru Adon; FX Armada Riyanto; Pius Pandor; Antonius Mangisengi (UIN Sunan Gunung Djati Bandung, 2022)
The Church believed that her faith had social relevance. God, who is believed in, is responded to in concrete cultural and political situations. Therefore, the Church is no longer an isolated religious institution but integral to people's life experiences. Currently, the Indonesian nation is not only in a political crisis but also a crisis of political behavior. This crisis is exacerbated because the political elite has no shame in politics. Empirically, it is effortless to find examples of how there is no sense of shame because they have been guilty in society, and most prominently in the attitudes of political elites. It is no secret that many leaders and political elites are guilty of causing various crises, but when appearing in public, they do not show that they are guilty. Thus, this study aims to find the ethical values of the passion story of Jesus based on the Gospel of John. John presents the story of Jesus' passion for showing Jesus' empire as King through His